성주지역 참외 바이러스병의 발생실태와 전염생태 - 박석진(Seok Jin Park); 이중환(Joong-Hwan Lee); 남문(Moon Nam); 박충열(Chung Youl Park); 김정선(Jeong-Seon Kim); 이주희(Joo-Hee Lee); 전은숙(Eun-Suk Jun); 이준성(Jun-Seong Lee); 최홍수(Hong-Soo Choi); 김정수(Jeong-Soo Kim); 문제선(Jae-Sun Moon); 김홍기(Hong Gi Kim); et al. (Sigmulbyeong yeon'gu, 2011)
Throughout the years 2008 to 2010, we analyzed approximately two thousand oriental melon samples collected from Seongju, using electron microscopy and testing by RT-PCR using primers specific for eight cucurbit-infecting viruses. Data from RT-PCR indicated that Cucumber green mottle mosaic virus (CGMMV), Watermelon mosaic virus 2 (WMV2) and Zucchini yellow mosaic virus (ZYMV) were present and the other viruses were not detected. Among them, CGMMV and WMV2 were the most prevalent pathogens. CGMMV was thought to infect oriental melon from the early growing season, and reached nearly 100% in the later of growing period. Otherwise, WMV2 emerged from June, several months later compared to CGMMV. CGMMV was detected from all aerial parts of the oriental melon including seeds, but not from the roots of the grafted pumpkin rootstock. Seed of two out of five commercial varieties were shown to be CGMMV positive. Nine varieties of pumpkins used as rootstocks were not infected with CGMMV. When the seedlings of grafted oriental melon were transplanted into pots mixed with the oriental melon debris infected with CGMMV, they were not infected by CGMMV. Cutting of pruning shear and the contact of tendrils contributed 48% and 30% to the transmission of the virus, respectively. 참외 주산지인 성주에서 2008년부터 2010까지 약 2,000점의 시료를 수집하였으며, 참외에 발생하는 바이러스를 동정하고 병 발생생태를 구명하기 위하여 전자현미경 검경과 박과 작물에 발생하는 8종의 바이러스, CGMMV, CMV, KGMMV, MNSV, PRSV, SqMV, WMV2, ZYMV의 종 특이적인 프라이머를 이용한 RT-PCR 방법으로 바이러스 감염 여부를 분석하였다. 그 결과 CGMMV, WMV2, ZYMV의 발병을 확인하였으며, 이외 5종의 바이러스는 발생하지 않는 것으로 조사되었다. 본 조사에서 성주 참외에서 발생하는 주요 바이러스는 CGMMV와 WMV2임이 확인되었다. CGMMV는 생육초기부터 발생하며 생육 후기에는 거의 대부분의 참외가 감염이 이루어졌다. 반면에 WMV2는 참외보다 몇 달 늦은 6월쯤에 발생이 이루어졌다. 이들 바이러스들은 최초 감염이 이루어지고 나면 생육하면서 급격히 확산되어 매우 높은 감염율을 나타내었다. CGMMV는 지상부 식물체 모든 조직에서 검출되었으나, 호박을 대목으로 사용한 뿌리 조직에서는 검출되지 않았다. 시판종자 5품종을 진단한 결과 3품종에서 CGMMV가 검출되었다. 참외의 대목으로 사용하고 있는 시판용 호박에 CGMMV를 접종한 결과, 바이러스에 감염되지 않았다. CGMMV에 감염된 참외 식물체를 분쇄하여 혼합한 토양을 통한 CGMMV의 전염은 확인할 수 없었으며, 덩굴손과 줄기와의 접촉, 전지가위를 통해서 각각 48%, 30%의 전업률을 나타냈다.